The role of environmental psychology in spatial strategic planning and design in Cheshmeh Aala in Damavand - Mahdi Fatemi; Faezehsadat Mousavibasir (مهندسی و مدیریت ساخت)
Cheshme Aala Damavand has natural and memorable areas that shines like a jewel in the city by providing suitable facilities in the welfare and tourism sectors and by having favorable capacities. In general, uncontrolled traffic in this sensitive natural environment, the presence of a large number of tourists, which is noticeable in the hot seasons of the year, lack of attention to the natural bed in the existing landscape around the site, bed pollution, especially the spring water and the stream flowing from it, the incompatibility of the constructions. Around the spring, the lack of provision of necessary services and issues related to health and cleanliness, the immediate proximity of residential areas and surrounding gardens to the recreation area around the spring are among the problems of this area. According to the topic of this article, which is considered a valuable natural environment, the presence of a large number of tourists in the region at times of the year, which is accompanied by problems; It makes it necessary to find a solution about it. According to the features of the project platform and the need to introduce it in order to identify the potentials, the research method in this article is descriptive and analytical and the analysis method is also based on the type of qualitative research. The design of the landscape around this natural spring, which is based on environmental psychology and rereading the cultural and natural context of the Alaa spring, can improve the native life and the natural environment, and somehow strengthen the bond between man and nature.